Depletion of stored nutrients during fasting in Nile tilapia (Oreochromis niloticus) juveniles - Nebo, Caroline [UNESP]; Gimbo, Rodrigo Yukihiro [UNESP]; Kojima, Juliana Tomomi [UNESP]; Overturf, Ken; Dal-Pai-Silva, Maeli [UNESP]; Portella, Maria Célia [UNESP] (Taylor & Francis, 2018)
We evaluated growth performance and metabolic responses in Nile tilapia (Oreochromic niloticus) juveniles (30.2 ± 0.9 g) subjected to 1 (F1), 2 (F2), or 3 weeks (F3) of fasting and then refed for 10 weeks (10WR) compared to controls (FC), which were fed for the full 13-week trial. Weight gain and specific growth rate (SGR) during fasting were lower in all treatments compared to the FC. However, during refeeding, feed intake/body mass and SGR increased in F1, F2, and F3, inducing partial compensatory growth. The hepatosomatic index (HSI), visceral fat index (VFI), liver glycogen (LG), and carcass lipid levels dropped in all fasted fish compared to FC (P < 0.05), showing a depletion of stored nutrients such as fat and LG. Along with LG, fat reserves were mobilized during fasting to maintain basal metabolism and survival, but these energy constituents returned to control levels at 10WR, at which time HSI was higher in all refed fish compared to FC. Additionally, the variables VFI, LG, and lipid in carcass increased in all refed fish, equaling those of FC at 10WR. The results showed that, in contrast with other protocols that used smaller tilapia juveniles, the feeding strategies utilized for Nile tilapia juveniles in this study (1 to 3 weeks of fasting and 10WR) were able to induce only partial compensatory growth. It can be concluded that in situations that require complete food restriction in juvenile Nile tilapia (30 g), an acceptable strategy is to limit the period of fasting to 1 week or less to minimize losses and to achieve partial compensatory growth.
Keywords: Compensatory growth; nutrient storage